Funders in Europe and incentivizing Open Science: Panel discussion - Brennan, Niamh; Proudman, Vanessa; Flæten, Jon Øygarden; Glinos, Kostas; Terry, Robert; Ruud, Kenneth (Septentrio Conference Series, 2019)
Watch the VIDEO. Funders across Europe are using scholarly communications to increase the impact of their grant results, thereby incentivizing researchers to share their research more openly. This panel session will start by describing the results of a research study called the RIF Project that gleans insights into the policy, rewards and incentives being employed by European research funders to encourage open access to publications and research data for the research they fund. The panel will then respond to the findings and will present and share experience on their policies. Funders across Europe are using scholarly communications to increase the impact of their grant results. More than 60 funders responded to a survey that was conducted in early Spring 2019 coming from key international funding bodies, national funding agencies, major charities and foundations, and national academies; from over 25 countries. The study was led by SPARC Europe in consultation with Science Europe, ALLEA and the EFC. Research Consulting conducted the research. The survey is the first of its kind, since it includes national funding agencies, academies, foundations and charities in Europe. What kinds of policy choices have funders made to influence how grantees increase open access to their research results with as few restrictions as possible? How can funders contribute to changing the research evaluation system by exploring ways to evaluate the intrinsic value of research beyond the impact factor for example, by promoting, and considering a wider range of types of research when evaluating grants? How are funders contributing to the investment in open, be it through financing OA journal articles and other material, and supporting infrastructure? The session will provide answers to these questions and will also raise awareness of the areas where funders can do more to strengthen their Open Science policies. Vanessa Proudman (SPARC Europe) will report on the results of the above-mentioned research study. Jon Øygarden Flæten (The Research Council of Norway), Kostas Glinos (The European Commission) and Robert Terry (World Health Organization and the Special Programme for Research and Training in Tropical Diseases) will present the views of their funder organizations. Kenneth Ruud (UiT The Arctic University of Norway) will speak on behalf of a research institution. Panel chair: Niamh Brennan (Trinity College Dublin).